Subjective Assessment of Knowledge and Health-Promoting Behaviors in the Area of Lower Urinary Tract Symptoms in Women - Małgorzata Wiśniewska; Karolina Chmaj-Wierzchowska; Katarzyna Tomczyk; Adrian Mruczyński; Maciej Wilczak; Katarzyna Wszołek (IMR Press, 2024)
Background: Lower urinary tract symptoms (LUTS) are a complex and widespread problem among women, resulting in serious problems in both physical, mental, and social health and occupational activity. Methods: A self-administered survey questionnaire was conducted among 100 women diagnosed with LUTS via Google Forms. Among other things, the level of knowledge and self-assessment of existing knowledge about the condition among affected women and the preventive activities undertaken were assessed. Results: The respondents' level of knowledge varied widely. The average score reached was 66.67% (64.48 ± 24.63%). The study demonstrated that women under 35 years of age (U = 772.5; p = 0.005) and those with higher education (U = 615.5; p < 0.001) had significantly higher levels of knowledge. Conclusions: Women's age and education affect knowledge of incontinence prevention. The common occurrence of lower urinary tract symptoms requires the development of a system of preventive, educational and therapeutic activities. Multilevel cooperation is important to increase the effectiveness of therapy.